2016
DOI: 10.1002/jaba.323
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in applied research on DRO procedures

Abstract: Citation for published item: f—rnetD w—rieEgl—ire @PHIIA illesEsls ssl—nds9 X ™—rtogr—phy of lives —nd de—ths ˜y egn es †—rd—F9D v9isprit ™r¡ e—teurFD SI @IAF ppF WUEIIIF Further information on publisher's website: httpsXGGdoiForgGIHFIQSQGespFPHIIFHHHH Publisher's copyright statement: gopyright ™ PHII v9isprit gr¡ e—teurF „his —rti™le (rst —ppe—red in v9isprit gr¡ e—teur SIFI @PHIIA WUEIIIF ‚eprinted with permission ˜y „he tohns ropkins niversity €ressF Use policy The full-text may be used and/or reproduced, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…However, prior research has suggested that responding is more likely to be eliminated in a full-session DRL (Jessel & Borrero, 2014), and elimination of the target response has been observed in applied research that used signals in a full-session DRL (Austin & Bevan, 2011). In fact, some researchers have characterized fullsession DRL schedules as variants of DRO schedules (Jessel & Ingvarsson, 2016). To address this, it may be possible to modify the full-session DRL procedure to protect against response elimination (e.g., require an exact number of responses to occur).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prior research has suggested that responding is more likely to be eliminated in a full-session DRL (Jessel & Borrero, 2014), and elimination of the target response has been observed in applied research that used signals in a full-session DRL (Austin & Bevan, 2011). In fact, some researchers have characterized fullsession DRL schedules as variants of DRO schedules (Jessel & Ingvarsson, 2016). To address this, it may be possible to modify the full-session DRL procedure to protect against response elimination (e.g., require an exact number of responses to occur).…”
Section: Discussionmentioning
confidence: 99%
“…In general, participants responded near optimal levels in the spaced‐responding DRL and at near‐zero levels in the full‐session DRL. These preliminary data suggest that full‐session DRLs may function more similarly to differential‐reinforcement‐of‐other‐behavior (DRO) schedules in that behavior is eliminated rather than simply reduced (Jessel & Ingvarsson, ). In the context of application, this suggests that desirable behavior could be inadvertently eliminated, and as a result, Jessel and Borrero urged against the use of a full‐session DRL in such circumstances.…”
mentioning
confidence: 99%
“…The DRO contingency has been proposed to reduce responding through several different processes (see Jessel & Ingvarsson, 2016 for a review), including, as the name suggests, the adventitious reinforcement of other behavior (Harman, 1973;Jessel, Borrero, & Becraft, 2015;Reynolds, 1961;Zeiler, 1970). The adventitious reinforcement hypothesis states that DRO schedules increase any response that immediately precedes the delivery of the reinforcers, resulting in the replacement of the target response.…”
mentioning
confidence: 99%
“…Further, contrast arrangements with DRO may yield information regarding the behavioral process responsible for behavior reduction. In a recent review of literature on DRO, Jessel and Ingvarsson ( ) described four processes or mechanisms implicated in DRO, one of which includes punishment. Some research (e.g., Rasmussen & Newland, ) suggests that behavior is influenced to a larger degree by aversive events than appetitive events.…”
Section: Research On Behavioral Contrastmentioning
confidence: 99%